Fitting of mathematical models in the drying of araticum (Annona crassiflora) seeds - ATAIDES, Iva Manoela Rocha; OLIVEIRA, Daniel Emanuel CABRAL DE; FERREIRA JUNIOR, Weder Nunes; RESENDE, Osvaldo; QUEQUETO, Wellytton Darci; ROMANI, Viviane Patrícia (Food Science and Technology, 2023)
Araticum (Annona crassiflora) seeds have relevant characteristics for industrialization due to the contents of phytosterols, carotenoids, phenolic compounds, fatty acids, and organic acids, among other components responsible for biological properties. The objective of this study was to fit different mathematical models to the experimental data, use criteria to choose the best model, evaluate the effective diffusion coefficient, and obtain the activation energy and thermodynamic properties of araticum seeds at different drying temperatures. Seeds of araticum fruits were dried at temperatures of 40, 50, 60, and 70ºC. The drying time of araticum seed decreases with increasing temperature. Among the best models fitted, the Midilli model was recommended to predict the drying curves of araticum seeds under different drying conditions. The linear model represented the effective diffusion coefficient as a function of the drying temperature. Enthalpy and entropy tend to reduce, and Gibbs free energy increases as the drying temperature increases.